A SOCIOLINGUISTIC ANALYSIS OF GENDER ON ENGLISH USE AT THE THIRD GRADE OF MTSN 2 PALU - Sri Deva; Nurdin; Khaerudin Yusuf (Datokarama English Education Journal, 2022)
The students at the third grade of MTs N 2 Palu have different social context in their life. Since different students in different societies have distinct ways of life, and language to a considerable degree is influenced by culture. The factors above against this background that this study is carried out to examine how the differences in English use of men and women and at the third grade of MTs N 2 Palu. This research discusses about the differences between men and women in using English. Considering the purpose of the research and the nature of the problem, this research was a qualitative-research. To collect the data the researcher used observation, interview, and video recording. The result of this study shows that the difference between the students in using English is influenced by the social context especially in cultural aspect. When the students use English, the accent of each culture follows into their English. It also affects the intonations and accent when they use English. While, the differences between men and women. Women found it easier to adjust their accents and distinguish accents from the culture and accents of the English. While, man found it difficult. So, when using English men are often carried away with accents from their own culture.